(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
Starting from the analysis of the only account book of the hospital of San Vincenzo in Prato left over, we reasoned about the patrimonial status of the institution and the administrative management implemented. The study, integrated with other sources preserved in the Archives of the Ospedale Maggiore, made it possible to reconstruct the Hospital connections with Milanese families and, consequently, to observe how it fitted into the economic and social system of the city of Milan. As it was drafted just a few years after the hospital and administrative reform that transformed the fifteenth-century Milanese health system, the account book also stands as witness to the economic status of one of those nine city hospitals that in 1458 were aggregated to the nascent Ospedale Maggiore, opening up the possibility of assessing the veracity of the accusations made against the hospital bodies that were among the motivations given for the centralization